Alveolar haemorrhage in ANCA-associated vasculitis: Long-term outcome and mortality predictors. Issue 108 (March 2020) - Quartuccio, Luca; Bond, Milena; Isola, Miriam; Monti, Sara; Felicetti, Mara; Furini, Federica; Murgia, Stefano; Berti, Alvise; Silvestri, Elena; Pazzola, Giulia; Bozzolo, Enrica; Leccese, Pietro; et al.
Abstract: Introduction: Alveolar haemorrhage (AH) is considered an important cause of morbidity and early mortality in anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitides (AAV). Objectives: The aim of this study was to identify predictors of outcome in patients with AH-AAV and to evaluate outcome and causes of death in this subset. Materials and methods: A multicenter retrospective study was conducted in 29 Italian Centers. Clinicians were asked to recruit all patients diagnosed with AAV-associated AH during the last 10 years, from 2007 to 2016. Univariate and multivariable analysis were performed. Results: One-hundred and six patients were included (median age at onset of 55 years [IQR 42–67]). The majority were ANCA-positive (PR3 57.1%, MPO 33.7%) and 72.6% had also renal involvement. At presentation, anaemia was shown in 97 (92.4%) patients, hemoptysis in 54 (51.9%), respiratory failure in 68 (66.7%), of whom 48 (70.6%), requiring respiratory support. At the end of the 37 months [IQR 13–77] follow-up, 19/106 (17.9%) patients were dead. The main causes of death were active disease and infections. By stepwise regression analysis, age >65 years (HR 3.66 [95% CI 1.4–9.51], p = 0.008) and the need for respiratory support (HR 4.58 [95% CI 1.51–13.87], p = 0.007) at AH onset were confirmed to be predictive of mortality. Conclusions: Predictors of outcome in AAV-AH were determined. Factors related to the patient's performance status and the severity of the lung involvement strongly influenced the outcome. Balancing harms and benefits for the individual patient in induction and maintenance treatment strategies is crucial. Highlights: This is the largest clinical description of alveolar haemorrhage in ANCA-associated vasculitis. Unexplained progressive anaemia in AAV should arise the suspicion of AH in AAV. Consider respiratory failure, age and cardiovascular comorbidity to manage AH in AAV in the short and long term.